Key to species of the genus Hengchunia Vilbaste (Hemiptera: Cicadellidae: Deltocephalinae), and with description of a new species from China - Xing, Ji-Chun; Dai, Ren-Huai; Li, Zi-Zhong (Zootaxa, 2010)
A new species Hengchunia hexaproducta sp. nov. is described and illustrated from China, representing the first record of the genus from the southeastern Palaearctic Region. A key is given to distinguish all species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).